This preview shows page 1. Sign up to view the full content.
Unformatted text preview: Ex. 4.4 3. (AB)C = A(BC) = | 250 68| | 75 55 | (a) k(A + B) =k[aij + bij] = [kaij + kbij] = [kaij] + [kbij ] = k[aij] + k [bij] = kA + kB (b) (g + k)A = (g + k)[aij] = [(g + k)aij] = [gaij + kaij ] = [gaij] + [kaij] = g [aij] + k [aij] = gA + kA ======================================= Ex 4.6 4. DF = Identity, thus D and F are inverses of each other EG = Identity, thus E and G are inverses of each other. =======================================...
View Full Document
- Spring '11